2011
DOI: 10.5098/hmt.v2.1.3008
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Heat Transfer From a Flat Plate With Shower Head Impinging Jets

Abstract: Conjugate heat transfer from a flat circular disk is investigated both computationally and experimentally with a constant heat flux imposed on its bottom surface and a shower head of air jets impinging on the top surface. The shower head consists of a central jet surrounded by four neighboring perimeter jets. Measured temperature data at twelve locations within the plate are compared with the conjugate heat transfer result obtained at the same locations computationally by Shear Stress Transport (SST) κ-ω turbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Nevertheless, even if the conjugate heat transfer is taken into account, there is some temperature gradient that exist between bottom and the top of the hot surface. The amount of temperature gradient will be larger for thick surface as compared to the thin surface [29]. Hence, the quenching of thin surface is much faster than the thick surface or the surface of 1 mm thickness attains the rewetting state much earlier than the surface of 3 mm thickness.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, even if the conjugate heat transfer is taken into account, there is some temperature gradient that exist between bottom and the top of the hot surface. The amount of temperature gradient will be larger for thick surface as compared to the thin surface [29]. Hence, the quenching of thin surface is much faster than the thick surface or the surface of 1 mm thickness attains the rewetting state much earlier than the surface of 3 mm thickness.…”
Section: Resultsmentioning
confidence: 94%
“…For a certain coolant flow rate and coolant temperature, the amount of energy available to be removed with thicker surface is larger as compared to the energy available with thinner surface. Several investigators have analytically evaluated the process of jet impingement surface quenching by considering the effect of conjugate heat transfer under transient and steady state condition [28][29][30]. The heat transfer characteristics of convective boundary layer flow over a flat plate are very much affected by the type of the thermal boundary conditions imposed at the top of the surface, which, is in contact with the fluid.…”
Section: Resultsmentioning
confidence: 99%
“…Behnia et al [13] reported that in the case of a single jet impingement, confined and free-surface jets provide nearly similar heat transfer coefficient when the jet exit to target spacing is more than the jet diameter. Confined or submerged multi jet configurations are also most suited for a closed loop system and such heat exchangers have been designed and tested by various researcher [14][15][16]. Fundamental studies on the thermohydraulics of a single submerged jet have been performed by Garimella and coworkers [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…Panda and Prasad [14] compared the performance of a five jet heat sink with a single jet with air as the heat transfer medium. For a fixed Reynolds number of 9500, the five jet heat sink gave more uniform surface temperature distribution than a single jet.…”
Section: Introductionmentioning
confidence: 99%
“…Gnanasekaran and Balaji (2011) developed a correlation for Nusselt number under turbulent mixed convection using transient heat transfer experiments. Panda and Prasad (2011) studied conjugate heat transfer from a flat plate with shower head impinging jets. Gonzalez et al (2012) made a numerical study of heat transfer by natural convection and surface thermal radiation in an open cavity receiver.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%